2016
DOI: 10.1016/j.teln.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Impacting Intent-to-Stay Teaching for Associate Degree Adjunct Clinical Nurse Faculty

Abstract: Background: The full-time nurse faculty shortage has resulted in nursing programs employing adjunct nursing faculty heavily into the clinical teaching component to fill the gap. Many adjunct faculty members continue to teach semester after semester; however, there is a lack of evidence to support the predictive factors that facilitate intent to stay teaching. Purpose: The purpose of this study was to better understand predictors of intent to stay teaching for associate degree (AD) adjunct clinical nurse facult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 88 publications
(486 reference statements)
2
8
0
Order By: Relevance
“…Finally, our study found that overall job satisfaction was a significant positive predictor of intent to stay (Table 3). The higher the job satisfaction, the more the respondents intended to stay in education, which was consistent with prior research 11,12 . When we examined each subscale's influence, job satisfaction and personal growth were approximately equal in their influence, followed by work preference.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Finally, our study found that overall job satisfaction was a significant positive predictor of intent to stay (Table 3). The higher the job satisfaction, the more the respondents intended to stay in education, which was consistent with prior research 11,12 . When we examined each subscale's influence, job satisfaction and personal growth were approximately equal in their influence, followed by work preference.…”
Section: Discussionsupporting
confidence: 86%
“…Herzberg's motivation‐hygiene theory provided the framework for understanding what contributed to job satisfaction and influence on intent to stay 10 . Overall, the study found a significantly positive correlation between job satisfaction and intent to stay, which is consistent with Herzberg's motivation‐hygiene theory and with the nursing literature 4,12,13 . Other significant findings of the study were average annual salary and whether faculty members were approached as an undergraduate to become an educator.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations